ANALISIS PENGAMBILAN KEPUTUSAN KARIR MAHASISWA DENGAN EKSPLORASI KARIR SEBAGAI PEMEDIASI - Nurrohim, Yusuf Teguh; Sumastuti, Efriyani; Setyorini, Noni (LPPM STIE Muhammadiah Bandung, 2023)
To obtain empirical data regarding the influence of conformity and self-efficacy on student career decision making, this research will examine careers as mediators for management students at PGRI University Semarang class of 2019. The population of this study was 270 students, and the sample was taken using the Sloviniformula of 163 people. The sampling method combines direct random sampling methodology with probability sampling. In this research, the data analysis used is PartialiLeast Squarei(PLS) analysis combined with Structural Equation Modeling (SEM) analysis. By utilizing SmarPLS 3.0 software, research data processing was carried out through the use of questionnaires. Hypothesis test findings clarify that (1) Career exploration is influenced by Self-Efficacy, (2) Career exploration is influenced by conformity, (3) Career decision making is influenced by Self-Efficacy, (4) Career decisions are influenced by conformity, (5) Decisions regarding careers are influenced by career exploration, (6) Through job investigation, Self-Efficacy influences the career decision making process, (7) Conformity impacts career exploration and decision making.